2012
DOI: 10.1039/c2ob07116a
|View full text |Cite
|
Sign up to set email alerts
|

Probing riboswitch–ligand interactions using thiamine pyrophosphate analogues

Abstract: The Escherichia coli thiM riboswitch forms specific contacts with its natural ligand, thiamine pyrophosphate (TPP or thiamine diphosphate), allowing it to generate not only nanomolar binding affinity, but also a high degree of discrimination against similar small molecules. A range of synthetic TPP analogues have been used to probe each of the riboswitch-ligand interactions. The results show that the pyrimidine-sensing helix of thiM is exquisitely tuned to select for TPP by recognising the H-bonding donor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 16 publications
4
66
0
Order By: Relevance
“…On the other hand, the addition of 500 μM TT ( 1 ) represses the expression of β–galactosidase expression to a level similar to that of thiamine. TT has been shown to depend on diphosphorylation to gain activity in vitro (Chen et al, 2012). Thus, we anticipate that TT is phosphorylated by the endogenous set of thiamine converting enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the addition of 500 μM TT ( 1 ) represses the expression of β–galactosidase expression to a level similar to that of thiamine. TT has been shown to depend on diphosphorylation to gain activity in vitro (Chen et al, 2012). Thus, we anticipate that TT is phosphorylated by the endogenous set of thiamine converting enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its close structural similarity to the natural substrate thiamine, TT is likely to be recognized and phosphorylated by endogenous bacterial enzymes such as ThiK. Using ITC measurements Chen and colleagues revealed that the chemically synthesized, diphosphorylated form of TT , named triazolethiamine pyrophosphate (TTPP), binds to the thiM (Figure 4A) riboswitch with an affinity of 370 nM, whereas for the natural ligand TPP a K D of 8 nM was measured (Chen et al, 2012). Additionally, in vitro translation assays proved that binding of TTPP induces a change in riboswitch secondary structure to sequester the SD-sequence and inhibits efficient protein translation (Chen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, as a cofactor of many enzymes which control bioenergetic [47–50], amino acid metabolism [51], and transformation of various carbohydrates, including pentoses, necessary for the synthesis of nucleotides [52]. Second, we cannot underestimate the non-coenzymatic role of phosphorylated derivatives of thiamine in control of cell metabolism by: allosteric regulation of enzymes [53,4749], transmission of nerve signals in synapses and likely involved in signaling pathways associated with receiving stimuli from the environment [54,55], and regulation of protein synthesis by so-called riboswitches in microorganisms and plants [56,57]. Finally, the results of many studies strongly suggest that thiamine, its phosphorylated derivatives, and thiamine-dependent enzymes play an important role in the reaction of microorganisms [58,59], animals [60,61], and plants [2,62] on various environmental factors like oxidative stress and pathogens.…”
Section: The Role Of Thiamine In the Basic Metabolic Pathways Of The mentioning
confidence: 99%